ANALISIS AKUNTANSI BIAYA LINGKUNGAN PADA PT. CAPLANG: ANALISIS AKUNTANSI BIAYA LINGKUNGAN PADA PT. CAPLANG - Moh Afrizal Miradji (.Universitas PGRI Adi Buana, 2022)
This research seeks to identify and analyze the techniques through which companies identify, quantify, present, and report environmental expenses in their financial statements. Utilizing qualitative primary data from interviews and quantitative secondary data from the company's financial accounts, the research was conducted at PT. Caplang. The corporation recognizes that environmental and operational expenses related with waste management are included in production costs due to the fact that trash is produced throughout the manufacturing process. according to each business's policies